Islamic Sustainability Modeling of Halal Startups in Indonesia Using Decision Tree Techniques - Agustiawan, Helma (Islamicate Institute, 2025)
The rapid growth of halal startups in Indonesia reflects increasing consumer demand for ethical, shar??ah-compliant goods and services. Despite this momentum, many startups face sustainability challenges stemming from limited access to Islamic finance, underdeveloped policy ecosystems, and a lack of integration with Islamic ethical frameworks. This study applies a conceptual decision tree methodology to identify the most critical factors influencing halal startup sustainability in Indonesia. Using qualitative data, the analysis incorporates variables aligned with maq??id al-shar??ah, such as founder religiosity, access to shar??ah-compliant capital, and ethical governance structures. Findings reveal that startups exhibiting alignment with Islamic values—particularly in funding, innovation, and management—demonstrate higher long-term viability. The decision tree model enables a systematic visualization of these relationships, providing theoretical and practical insights for entrepreneurs, policymakers, and Islamic economists. This approach contributes to Islamic economics by demonstrating how normative frameworks can be transformed into predictive models that support ethical entrepreneurship across Muslim markets.